Outcomes following extra-articular fractures of the scapula: A systematic review. Issue 3 (March 2020) - Bi, Andrew S.; Kane, Liam T.; Butler, Bennet A.; Stover, Michael D.
Highlights: This study is the largest systematic review evaluating outcomes following purely extra-articular scapula fractures. Extra-articular scapular fractures treated operatively had union rates from 94.7 – 100%, complication rates of 14.4% and Constant scores of 84.4. Extra-articular scapular fractures treated conservatively had union rates from 75 – 90.2%, complication rates of 3.4% and Constant score of 79.0. All extra-articular scapular fractures had forward elevation greater than 150° at final follow up regardless of operative versus non-operative treatment. There is a severe lack of high-quality comparative studies between operative and nonoperative management of extraarticular scapular fractures. Abstract: Background: Scapular neck and body fractures are typically treated nonoperatively, with operative treatment traditionally focused on intraarticular fractures or double disruptions of the shoulder suspensory complex. The objective of this study was to systematically examine and compile the existing literature in regard to operative and conservative treatment of extraarticular fractures of the scapula. Methods: A comprehensive search of multiple electronic databases was performed according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement to find outcome data on fractures of the scapular neck and body. All studies from 1988 to 2018 that met inclusion criteria were reviewed independently and graded based on the modified Coleman Methodology Score. Outcomes of interest were compiled and analyzed for adjusted means. Results: 42 manuscripts with a total of 669 patients were included for analysis from an initial search of 335 results. There was an average age of 41.2 years, 78.1% were male, 98.8% had a blunt force mechanism, and 66.7% had other injures outside the scapula at time of presentation. In total, there were 120 patients with scapular body fractures, 95 with scapular neck fractures, 130 with floating shoulder injuries including a scapular neck or body fracture, and 324 with an unspecified extraarticular scapular fracture. 464 patients were treated operatively, with a mean union rate of 99.4%, Constant score of 84.4, and end forward elevation of 158°. 205 total patients were treated non-operatively, with a mean union rate of 85.1%, Constant score of 79.0, and end forward elevation of 153°. Conclusion: Patients with extraarticular fractures of the scapula have excellent outcomes following either nonoperative or operative management. There is a need for high quality comparative studies to determine the optimal treatment strategy for these injuries.